Founding mothers of Chueta population. (December 2015) - Ferragut, J.F.; Marques, S.L.; Ramon, C.; Castro, J.A.; Amorim, A.; Alvarez, L.; Picornell, A.
Abstract: In the present work, we studied 109 unrelated Chueta individuals aiming to characterize their maternal gene pool composition. The entire mtDNA control region (1121 bp) was sequenced. The highest frequencies were found for haplogroups R0a and H, indicating a remarkable signature of Middle Eastern ancestry along with some degree of European admixture. These data confirm that Chuetas have been able to maintain some ancestral genetic identity. The significant differences with their host population should therefore be taken into account in forensic casework.